Sociología general/sociología del derecho o jurídica. Problemas de su concepción - Mendoza Herrejón, María Blanca Estela (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
General Sociology / Sociology of Law or Legal. Problems of conception, is the title of this work, we have called so, because for us, in fact, the mother science as their specialty, were suffering from conception, that is, identity and scientific dimension is confusing; untreated confusion and inadequate development conducive addressed in their respective fields of study and research; which in turn makes it difficult to move at their scientific consolidation; thus confusing the object of study, study methods, orientation and function of their studies, fields of study of other sciences with which there must be a reciprocal and proper relationship and aid to a better understanding of reality is invaded social; in our case particularly with the law. This is because the importance and interest in the topic was our consideration, hoping its importance is understood, raise interest and generate debate on it among students of Sociology, Sociology of law or legal and Law; reiterating in our particular case, for their relationship and help with the latter. The treatment of the subject is as follows: As regards the issue conception facing Sociology, treatment we have organized according to three aspects, namely: first, in terms of its method of study, we question what science is this: it is a natural science or, it is a cultural science (or spirit), or is a formal science or is a behavioral science; second, in their orientation study, we question what kind of science is the General Sociology: it is a purely empirical science or is a purely theoretical or science, is a theoretical empirical science and is an empirical science or practice is practical or theoretical science, is a theoretical and practical-empirical science; finally from the third aspect, in terms of its function, we question what kind of science is the General Sociology is an empirical and practical science or is a theoretical and practical or science is a-theoretical and practical empirical science or is a empirical and practical-normative-critical or theoretical science is a critical-normative science or is a practical-theoretical and empirical-critical-normative science.

Sociología General/Sociología del Derecho o Jurídica. Problemas de su concepción, es el título de este trabajo, lo hemos titulado así, porque para nosotros, en efecto, tanto la ciencia madre como su especialidad, padecen problemas de concepción, es decir, su identidad y dimensión científica es confusa; confusión que de no tratarse y atenderse propicia un inadecuado desarrollo en sus respectivos ámbitos de estudio e investigación; lo que a su vez, dificulta que avancen a su consolidación científica; pues al confundir su objeto de estudio, sus métodos de estudio, su orientación y su función de sus estudios, se invade campos de estudio de otras ciencias con las que debe haber un recíproca y adecuada relación y auxilio, para la mejor comprensión de la realidad social; en nuestro caso particular con el Derecho. Esta es pues, la importancia e interés que en nuestra consideración el tema reviste, esperando se comprenda su importancia, despierte el interés y genere el debate sobre el mismo, entre los estudiosos de la Sociología General, de la Sociología del Derecho o jurídica y del Derecho; reiterando en nuestro caso particular, por su relación y auxilio con este último. El tratamiento del tema es el siguiente: Por lo que se refiere a la problemática concepción que enfrenta la Sociología General, su tratamiento lo hemos organizado atendiendo a tres aspectos, que son: primero, en cuanto a su método de estudio, nos cuestionamos qué tipo ciencia es ésta: es una ciencia natural o, es una ciencia cultural (o del espíritu) o, es una ciencia formal o, es una ciencia de la conducta; segundo, en cuanto a su orientación de estudio, nos cuestionamos qué tipo de ciencia es la Sociología General: es una ciencia puramente empírica o, es una ciencia puramente teórica o, es una ciencia empírica teórica o, es una ciencia empírica práctica o, es una ciencia teórica práctica o, es una ciencia empírica-teórico-práctica.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2016-0074; Identidad; Dimensión científica; Adscripción científica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/695